Insolvency Test As Protection For Public Companies From Declaration Of Bankruptcy - Tranggono, Emiral Rangga; Wijaya, Mustika Mega; Insan, Isep H (PALAR (Pakuan Law review), 2025)
AbstractThe ease of filing a bankruptcy petition in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (Bankruptcy Law PKPU) creates vulnerabilities for public companies, even though the public companies have good intentions and healthy financial conditions. The absence of insolvency test regulations creates a legal vacuum that has the potential to be misused by creditors. This study aims to examine the urgency of implementing an insolvency test in Indonesian bankruptcy law and to analyze the need for legal protection for public companies that are still solvent from the potential misuse of bankruptcy petitions through the application of an insolvency test. The research method used is normative law, which uses a legal norm system, which includes research on legal principles and legal rules, in addition this study uses a descriptive inductive approach. Public companies whose shares are owned by many investors need legal protection so that the shareholder community is also protected. The use of insolvency tests such as the balance sheet insolvency and cash flow insolvency methods can be an objective basis for the court in deciding on bankruptcy petitions against public companies. The absence of regulation on insolvency test in Bankruptcy Law PKPU is the impetus to reform bankruptcy law in Indonesia. Therefore, there needs to be a provision that requires bankruptcy test before a public company can be filed for bankruptcy, to ensure that its financial condition is truly insolvent. Keywords: Public Company; Bankruptcy; Insolvency Test.